Evolution of efficiency in electricity markets - Tiryaki, Cuma Sani. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This study aimed to analyse the change in efficiency in spot and future electricity markets in selected European countries through the measured period considering the market couplings. We have analysed ten different countries' spot and futures markets using five efficiency measures. We have used entropy measure to understand the randomness in the markets. Our tests to calculate the Hurst measure has aimed to capture the long-term memory in the price series. We used fractal dimension to measure the roughness and irregularity of price series. Ex-post risk premiums are calculated to understand the spot and future market relations. Expected spread analysis has provided insight regarding the liquidity in the markets. Based on quantitative analysis, we can conclude that these markets carry some common characteristics. We can also point out that there is progress towards less inefficiency in the markets, especially after introducing structural and regulatory changes. Application of moment statistics and regularity statistics on such a data set helps make broader deductions. Finally, our results provide insight into the expected structures of other markets if they follow similar developments.
Keywords: Electric utilities -- Marketing.; Electric industries.